PENGGUNAAN MAJAS DALAM PUISI MENGGUNAKAN MEDIA LAGU SISWA KELAS VIII SMP NEGERI I GUNUNG TALANG - Hasmi Novianti (STKIP ROKANIA, 2017)
This study aimed to describe the type of figure of speech what are contained in the poem by media songs written by VIII.5 grade students of SMP N 1 Gunung Talang. This research is a qualitative study using descriptive methods. The sample was VIII.5 grade students of SMP N 1 Gunung Talang by the number of students 30 people. Data of this study is the result of the test write poetry using the medium of songs written by the sample. Based on the results, it can be concluded that the figure of speech contained in the poem VIII.5 grade students of SMP N Gunung Talang broadly grouped into four, namely the comparative figure of speech, opposition, interlacing and looping. Majas comparison consists of a figure of speech personification figure of speech parable 15 usage and 17 use. Majas opposition consists of the use of hyperbole and litotes 7 4 use. Majas linkage consists of sinekdoke 1 use, allusion 9 use and inversion one use. Majas iteration consists of one use of alliteration and repetition 9 use